Cuidado humanizado por el personal de salud durante la atención del trabajo de parto Estrategias más utilizadas (2021)
It´s necessary to implement humanized childbirth as a model of childbirth care, this allows taking into account the opinions, needs and personal characteristics of the pregnant woman and her family, so that the intervention of the professional is provided according to their needs. Objective: To identify in the literature the most used strategies to promote humanized care by health personnel during labor care. This information is based on the review of 40 articles, where 10 documents were eliminated, and 7 of them were graduate theses, 2 were articles that incorrectly judge the humanization of labor and 1 of them was carried out quantitatively but does not provide relevant information for the research, therefore the analysis was carried out with 30 articles in Spanish, English and Portuguese. The use of any strategy or alternatives for the humanization of childbirth in addition to favoring the tranquility of the pregnant woman